(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to comprehensively examine and analyze the concept of student intelligence from an Islamic educational perspective. The study employed a qualitative descriptive approach with a library research approach. Data were obtained from primary sources, including the Qur’an, Hadith, and primary literature on Islamic education and intelligence theory. Secondary data were obtained from books, scientific journals, and relevant previous research. Data collection was conducted through documentation studies, while data analysis employed content analysis techniques, comprising data reduction, classification, interpretation, and conclusion drawing. The results indicate that Islamic education views intelligence not only as an intellectual aspect (IQ), but also encompasses emotional (EQ), spiritual (SQ), and the complex potential of human beings integrated into the dimensions of ’aql, qalb, ruh, and badand. Islam places intelligence as a gift from Allah SWT that must be developed in a balanced manner through holistic education. Strategies for developing student intelligence in Islamic education include integrating the values ​​of monotheism, cultivating tadabbur and tafakkur, and fostering Islamic character in the learning process.